Electroabsorption studies of organic p-i-n solar cells: Evaluating the built-in voltage - Siebert-Henze, E; Lyssenko, V; Brückner, R; Riede, M; Leo, K (Materials Research Society, 2014)
We investigate the built-in voltage in organic bulk heterojunction solar cells using electroabsorption spectroscopy based on the Stark effect, i.e. the variation of the absorption energies of a material caused by an electric field. Due to spectral contributions of permanent dipoles, a novel approach for evaluating the EA spectra is required. We use a fitting routine analyzing a broad spectral range instead of using only a single wavelength. A reliable quantitative determination of the built-in voltage is achieved. Copyright © Materials Research Society 2014.